MBCT (Mindfulness Based Cognitive Therapy) terhadap Stres dan Kopingsindrom Pramenstruasi (Journal of Telenursing (JOTING), 2024)
This study aims to determine the effect of MBCT (Mindfulness Based Cognitive Therapy) intervention on stress and coping with premenstrual syndrome. The research method is a quasi-experiment within two groups with a pretest-posttest control group design. The results showed that the Mindfulness-Based Cognitive Therapy (MBCT) Intervention affected stress (p 0.000